Paper-based microfluidic devices: A complex low-cost material in high-tech applications. (10th May 2017) - Böhm, A.; Biesalski, M.
Abstract: Abstract : Paper is a material made from renewable resources, and it has been used intensively for almost 2000 years. It is a highly porous, bendable, and foldable flat structure of randomly arranged and connected fiber-like basic building blocks. The capability to transport fluids without pumps and sophisticated dosing systems is attractive. Paper microfluidics especially has gained increasing interest, particularly in the last decade. Although a number of interesting demonstration devices for easy-to-use diagnostic systems have been reported, only a limited number of these have found applications. This is mainly due to the geometric and chemical complexity of the material. While chemical functionalization (e.g., for defining hydrophobic barriers for spatially resolved fluid transport) is well advanced, understanding and controlling capillary-driven transport of a fluid within the complex porous matrix of paper. This article highlights recent advances and outlines design strategies for successful microfluidic paper-based applications.